The uncertain role of substandard and falsified medicines in the emergence and spread of antimicrobial resistance - Cavany, S; Nanyonga, S; Hauk, C; Lim, C; Tarning, J; Sartorius, B; Dolecek, C; Caillet, C; Newton, PN; Cooper, BS (Springer Nature, 2023)
Approximately 10% of antimicrobials used by humans in low- and middle-income countries are estimated to be substandard or falsified. In addition to their negative impact on morbidity and mortality, they may also be important drivers of antimicrobial resistance. Despite such concerns, our understanding of this relationship remains rudimentary. Substandard and falsified medicines have the potential to either increase or decrease levels of resistance, and here we discuss a range of mechanisms that could drive these changes. Understanding these effects and their relative importance will require an improved understanding of how different drug exposures affect the emergence and spread of resistance and of how the percentage of active pharmaceutical ingredients in substandard and falsified medicines is temporally and spatially distributed.